Does the COVID-19 crisis mark a turning point on the apprenticeship market? : A forecast of the possible development of new apprenticeship contracts up until 2030 - Maier, Tobias [Verfasser] (My University, 2021)
"In the wake of the COVID-19 crisis, the number of newly concluded apprenticeship contracts in 2020 decreased by 57,600 compared to the previous year to reach the lowest level recorded since 1975. This article demonstrates that this collapse was only so severe because a surprisingly large amount of young people, particularly those in possession of a higher education entrance qualification, had commenced company-based training in the three years preceding. From a demographic perspective, the low level of training contracts was predictable. The question arising in future will be whether the transition rates of the young people stay at the low level of 2020 and what the long-term implications of this will be in regard to securing a supply of skilled workers." (author's abstract; BIBB-Doku)
Markiert die COVID-19-Krise einen Wendepunkt auf dem Ausbildungsmarkt? : Ein Ausblick auf die mögliche Entwicklung neuer Ausbildungsverträge bis 2030
Keywords: G 1.3.1.1 Ausbildungsstellenmarkt; G 1.3.2.2 Übergänge; 370; Berufsausbildung; Ausbildungsstellenmarkt; Pandemie; Einmündungsquote; Projektion